METHODS OF PROTECTING INTELLECTUAL PROPERTY IN UZBEKISTAN: TRADEMARK AND LEGAL BASIS FOR ITS USE (American Journal of Pedagogical and Educational Research, 2025)
This article analyzes the methods of protecting intellectual property in Uzbekistan. In particular, it provides information on the registration and protection of trademarks in Uzbekistan, an analysis of regulatory legal acts regulating the field of intellectual property, and the existing practice. Specific features and terms of trademark registration are one of the most pressing issues discussed in this article. It also describes the legislative problems related to the topic under discussion and the author's proposals for solutions to these problems.